(untitled) (Archive of Conferences, 2022)
The article describes the movement of the looms on the loom, analyzes the effect of yarn tension on the loom during the formation of the loom, the main parameters of the loom on the loom, changes in the values of the loom tension. There are also diagrams of the position of the scales in relation to the sternum when laying the fabric on the loom, the density of the fabric produced, ie the density of the back, the type of weaving, the movement of the scales vertically with respect to the length of the scales